Physiological and Hormonal Effects of Titanium Dioxide Nanoparticles on Thyroid and Kidney Functions (Baghdad Science Journal, 2023)
Titanium dioxide nanoparticles (TiO2 NPs) are generally used in different types of applications such as the industry of plastics, paper industry, paints, toothpaste, cosmetics, sunscreens, and in various lifestyles, because of the vast range of applications and our daily exposure to these nanoparticles and a lack of information on animal and human health this study was designed to reveal dose and time-dependent effects of TiO2-NPs on the thyroid gland and kidney functions in male rats.For this study 54, Sprague-Dawley albino adult male rats were classified into three main groups each of 18 rats treated for a particular duration (1,2, and 4) weeks respectively. Each group was subdivided into three subgroups each of six rats treated as follows; group (1) serve as normal control, group (2, and 3) intra-peritoneal treated with TiO2NPs (50,200) mg/kg respectively, rats are dissected at the end of each experiment and the weights of thyroid and kidney is measured. The result showed a highly significant decrease (p<0.01) in the thyroid gland and a highly significant increase (p<0.01) in kidney weights and TSH, blood urea, creatinine, and total protein, while a highly significant decrease (p<0.01) inT3 and T4 in all different doses (50,200) mg/kg at durations 1, 2 and 4 weeks. The outcomes of the present study illustrate a significant decrease in serum levels of T4 and T3 with exposure to TiO2 NPS which disrupts thyroid function, while TiO2 NPS raises the level of urea, total protein, and creatinine. This could be related to the high dose of TiO2-NPs and duration of the study, which caused degeneration and necrosis of kidney cells and damage to peritubules that led to the prevention of secretion which raised urea levels in the blood, also led to high levels of creatinine and total protein in serum because of the imbalance that occurred in the kidney functions.